The relationships between notochord and floor plate in vertebrate development revisited - Teillet, M.-A. (National Academy of Sciences, 1998)
By using the quail–chicken chimera system, we have previously shown that during development of the spinal cord, floor plate cells are inserted between neural progenitors giving rise to the alar plates. These cells are derived from the regressing Hensen’s node or cordoneural hinge (HN-CNH). This common population of HN-CNH cells gives rise to three types of midline descendants: notochord, floor plate, and dorsal endoderm. Here we find that HNF3β, an important gene in the development of the midline structures, is continuously expressed in the HN-CNH cells and their derivatives, floor plate, notochord, and dorsal endoderm. Experiments in which the notochord was removed in the posterior region of either normal chicken or of quail–chicken chimeras in which a quail HN had been grafted showed that the floor plate develops in a cell-autonomous manner in the absence of notochord. Absence of floor plate observed at the posterior level of the excision results from removal of HN-CNH material, including the future floor plate, and not from the lack of an inductive signal of notochord origin.